Analysis of the Adoption Level of Qris in West Papua: The Roles of Self-Efficacy, Personal Innovativeness, and Privacy Concern - Samberi, Irianti; Inan, Dedi Iskandar; Wurarah, Rully Novie; Juita, Ratna; Sanglise, Marlinda (STMIK Banjarbaru, 2024)
The increased use of QRIS, especially in Manokwari, warrants research to understand the adoption intention along with several determining factors. The research aims to understand the influence of Self-Efficacy, Personal Innovativeness, and Privacy Concern on the adoption of QRIS in the West Papua Province. This research utilizes the Technology Acceptance Model (TAM) with perceived usefulness and perceived ease of use, external variables such as Privacy Concern, Personal Innovativeness, Self-Efficacy, and control variables are measured through SEM-PLS. An online questionnaire was distributed to the West Papua community, with 162 respondents who had used QRIS in the past month. The research results indicate that Self-Efficacy and Personal Innovativeness significantly affect perceived usefulness and perceived ease of use. Privacy Concern influences Adoption intention, which subsequently affects perceived usefulness and perceived ease of use. However, the relationship between Privacy Concern and perceived usefulness and perceived ease of use is less significant, indicating that the perception of Privacy Concern is not a major factor in the adoption of QRIS in West Papua Province.Keywords: Mobile Self-Efficacy; Personal Innovativeness; Privacy Concern; QRIS; SEM-PLSÂ AbstrakAdanya peningkatan penggunaan QRIS khususnya di Manokwari sehingga perlu dilakukan penelitian untuk mengetahui niat adopsi dengan beberapa faktor penentu. Tujuan penelitian adalah memahami pengaruh Self-Efficacy, Personal Innovativeness, dan Privacy Concern terhadap adopsi QRIS di Provinsi Papua Barat. Penelitian ini menggunakan model Technology Acceptance Model (TAM) dengan perceived usefulness & perceived ease of use, variabel eksternal seperti Privacy Concern, Personal Innovativeness, Self-Efficacy, dan kontrol variabel diukur melalui SEM-PLS. Kuesioner online disebarkan kepada masyarakat Papua Barat, dengan 162 responden yang pernah menggunakan QRIS dalam satu bulan. Hasil penelitian menunjukkan bahwa Self-Efficacy dan Personal Innovativeness berpengaruh signifikan terhadap perceived usefulness dan perceived ease of use. Privacy Concern mempengaruhi Adoption intention, yang kemudian mempengaruhi perceived usefulness dan perceived ease of use. Namun, hubungan Privacy Concern dengan perceived usefulness dan perceived ease of use kurang signifikan, menunjukkan bahwa persepsi Privacy Concern tidak menjadi faktor utama dalam adopsi QRIS di Provinsi Papua Barat.Â